TINJAUAN HUKUM TERHADAP ADVOKAD DALAM MELAKUKAN PENGAJUAN PERMOHONAN PENANGGUHAN PENAHANAN DENGAN JAMINAN ORANG - Muh. Nasir (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
Legal review of advocates in doing suspension of application of warranties with arrest people (Study In The Office Peradi Gorontalo City), The Obstacles Faced Advocates In Doing Filing Request Suspension Detention With Assurance Person. The theme options against the background because there is no definite arrangement on the Crime of what can be done surety that led to injustice and cause problems, for example, by an initial survey conducted by the Detention Suspension PERADI pengguhan Gorontalo There are 12 cases of detention on bail by the year 2014- 2015. Of the eight (8) cases occurred in 4 cases declined over the suspension of his detention. Such reference to the above, of course there are constraints that caused the rejection of the application for suspension of detention, the reasons are needed to do more in-depth research on the application for suspension of detention on bail filed by the Advocates. This study aimed to identify and analyze what the problem Advocates of doing filing of applications for suspension of detention on bail people and also to analyze and determine what Advocate efforts in tackling the obstacles that arise. This type of approach is used to understand, simplify as well as facilitate the Law is an empirical study using sociological juridical approach. Primary Data Obtained by conducting a live interview with the Advocate PERADI Gorontalo ever do surety. While the secondary data obtained by obtaining the data using written sources, namely by searching files surety that ever done PERADI Gorontalo to be able to obtain the amount of the surety who've done PERADI Gorontalo, legislation, literature relating to Constraint faced Advocates In Doing Filing Request Suspension Detention With Assurance person.